I've Got Your Number - Kinsella, Sophie (London Bantam Press, 2012)
I've lost it. :(The only thing in the world I wasn't supposed to lose. My engagement ring. It's been in Magnus's family for three generations. And now, the very same day his parents are coming, I've lost it. The very same day. Do not hyperventilate, Poppy. Stay positive!! :) A couple of glasses of bubbly with the girls at a charity do and Poppy's life has gone into meltdown. Not only has she lost her engagement ring, but in the panic that followed, she's lost her phone too. As she paces shakily round the hotel foyer she spots an abandoned phone in a bin. Finders keepers! Now she can leave a number with the hotel staff. It was meant to be! Except the phone's owner, businessman Sam Roxton, doesn't agree. He wants his phone back, and doesn't appreciate Poppy reading all his messages and wading into his personal life. As Poppy juggles wedding preparations, phone messages and hiding her left hand from Magnus and his parents, can things get any more tangled?
Keywords: Cell Phone Theft -- Young Women